Adherence to treatment among hypertensive individuals in a rural population of North India - Misra, Puneet; Salve, Harshal Ramesh; Srivastava, Rahul; Kant, Shashi; Krisnan, Anand (Indian Journal of Community Health, 2017)
Background: Hypertension affects nearly a quarter of adults in India. While there are issues related to diagnosis and treatment gap, even among those who received treatment, adherence is a problem resulting in poor control. Aim & Objective: To study the adherence to treatment of hypertension and its determinants among rural population Methods and Material: A community based cross-sectional study was carried out in twenty-eight villages in Ballabgarh block of Faridabad district of Haryana. Sample size of 300 was calculated. Adults (? 18 years) with self-reported hypertension were recruited by simple random sampling at community level. Adherence to treatment was studied by both recall and pill count methods. Information about socio-demographic characteristic was also obtained. Results: In total 350 participants were recruited in the study. Adherence (100%) by recall method was reported among 27.4% subjects and by pill count among 18.9% subjects. Symptom-free period was identified as most common reason for non-adherence. Statistically significant poor adherence to treatment of hypertension was reported among subjects belonging lower social strata. Conclusions: Very low adherence to hypertension treatment was reported in rural community in northern India. There is urgent need for awareness generation about treatment adherence and developing adherence-monitoring mechanisms at community level